Diversity, Biomass and Carbon Stock of Weed Species in Oil Palm Plantation - Sharifah Mazenah, Binti Wan Yusuf (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Oil palm plantation is one of the largest commodities in Malaysia and weeds are considered as one of the major component in the plantation while involve in global carbon cycle. Weeds play important roles in plantation where weeding strategy is crucial in promoting higher production yields and a better and understanding of weed is needed. This study was carried out at Malaysia Palm Oil Board, Sungai Asap, Belaga, Sarawak at three different areas of 20 years old seconday forest, newly planted and five years old oil palm plantation to show the conversion of land before land clearing until 5 years old of planting areas in oil palm plantation. The objectives of this study were to determine species diversity, biomass and carbon stock estimation of weed species by using two different methods of estimation; Pearson (2005) and CHN Analyser. A total of 100 quadrate, measuring 1m × 1m were thrown in each area with systematic random placed and all weeds were identified, counted, recorded, dried for dry weight determination and were oven-dried at 60⁰C for at least 7 days. A total 3304 individuals belonged to 97 species were found in 20 years old secondary forest while 9640 individuals belonged to 112 species and 7662 individuals in 91 species were enumerated in newly planted and 5 years old oil palm plantation areas respectively. In term of diversity, newly planted area had the highest species diversity (H’ 3.3815) with species evenness (J’ 0.7166) as compared to 20 years old secondary forest (H’ 3.2950) with species evenness (J’ 0.7203) while the least 5 years old oil palm plantation (H’ 2.9664 and J’ 0.6572). Meanwhile, all areas shared different patterns of growth forms contributed by herbaceous, tree species, shrubs, vines, ferns, grasses and sedges. In all weeds recorded, perennials were mostly found than annuals as well as broadleaf weed species was obviously seen in both areas. The dominant iv species in 20 years old secondary forest understory were Pteris ensiformis Burm., (SDR = 8.7679), Scleria sumatrensis Retz. (SDR = 7.8746), Digitaria ciliaris (Retz.) Kuel. (SDR = 6.9783), Taenitis blechnoides (Willd.) Sw.c(SDR = 5.6330), Centotheca lappacea (L.) Desv. (5.3786). In newly planted area, Trema cannabina Lour. was the most dominant species having highest SDR value (SDR = 9.2271) followed by Scleria sumatrensis Retz. (SDR = 7.4970), Mikania micrantha H.B.K (SDR = 6.8472), Tetrastigma indicum (SDR = 5.2449) and Paspalum conjugatum Berg. (SDR = 5.2387) while in 5 years old area it showed the dominance of Asystasia intrusa Bl. with the highest SDR value of 15.3390 and being the most dominant for species found in the area. It was followed by species of Axonopus compressus Beauv. (SDR = 10.9042), Mikania micrantha H.B.K (SDR = 7.9489), Nephrolepis biserrata (Sw.) Schott (SDR = 6.7723) and Scleria sumatrensis Retz. (SDR = 5.6574). A new percentage of 39.89% (fraction 0.3989) carbon content was determined from analysis of CHN Analyser to be compared with 50% (fraction 0.5) (Pearson et al., 2005). Therefore, for 20 years old secondary forest understory, about 1.7326 ton ha-1 was estimated by using Pearson’s (2005) method as compared to 1.3823 ton ha-1 by using new fraction of CHN Analyser while in newly planted area, a total of 6.0422 ton ha-1 of (Pearson et al., 2005) as compared to only 4.8204 ton ha-1(CHN Analyser) as well as 4.6600 ton ha-1 (Pearson et al., 2005) and 3.7178 ton ha-1 (CHN Analyser) of carbon stock was estimated in 5 years old oil palm plantation. Thus, an accurate adjusted formula was needed to estimate carbon stock of tropical weed species and more research is important on local and functions to yield better national estimates of carbon storage and sequestration.